G. gnemon KEANEKARAGAMAN MORFOTIPE EKTOMIKORIZA DAN STRUKTURNYA PADA MELINJO (Gnetum gnemon) DI CAGAR ALAM LAMEDAI, KOLAKA - basrudin basrudin; Sahindomi Bana; Markus (Jurusan Kehutanan -FHIL-UHO, 2023)
This research focuses on the diversity of ectomycorrhizal morphotypes and their structures in Melinjo trees (Gnetum gnemon) found in the Lamedai Nature Reserve, Kolaka. The study aims to comprehend the complexity of the symbiotic relationship between Melinjo and ectomycorrhiza, and to identify and analyze the existing variations in ectomycorrhiza morphotypes. Data collection methods include field surveys and morphological microscopic analysis. Melinjo forms five ectomycorrhizal morphotypes with characteristics such as simple white, simple dark gray, tawny monopodial pinnate, dark red irregular pinnate, and fawn irregular pinnate. The simple white morphotype showed a relatively high abundance and a significant species richness index, with a root colonization percentage reaching 33.09%. Ectomycorrhizal diversity in Melinjo was assessed as moderate with an index value of 1.79. It is hoped that the results of this research will provide in-depth insight into the role of ectomycorrhiza in the Melinjo ecosystem in the region, as well as its contribution to the diversity of soil microbiota flora